HYDROGRAPHIE SOME FACTUAL AND LEGAL DIMENSIONS OF THE FENOMENON “TRAFFICING IN HUMAN BEINGS”: HYDROGRAPHIE SOME FACTUAL AND LEGAL DIMENSIONS OF THE FENOMENON “TRAFFICING IN HUMAN BEINGS” - Nikolova, Yana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The report examines some factual and legal aspects of the fenomenon of human trafficking.The factual and normative manifestations are considered as interpenetrating indivisibility. The legal essence of the crime “human trafficking” is clarified, and its main composition is analyzed. Parallels have been drawn with nearby phenomena, somethimes leading to trafficking – migration and channeling. The social aspects of the phenomenon are analyzed and a multidisciplinary approach is proposed to deal with the problem threatening migrationnational security.